Gendered Spaces and Female Resistance: Virginia Woolf’s ‘The Mark on the Wall’ - Sacido Romero, Jorge; Lojo Rodríguez, Laura M. (Miscelánea: A Journal of English and American Studies, 2006)
Virginia Woolf’s conviction that space is never a neutral emptiness, but a web of cultural, social and ideological relations is the issue at stake in the present paper. Gender and space are constructed as mutually dependant categories, and, as far as Woolf was concerned, both appear in need of revision and rethinking. Woolf’s short story “The Mark on the Wall”, published as early as 1917, dramatises such a need, while advancing certain ideological assumptions embodied in a particular imagery which will reappear in some of her later work. The mark on the wall, both the title and the key image which structures the narrative, emerges as a disturbing block that threatens to diminish order and coherence within the confines of the space which the traditional living-room entails, by focusing on the narrator’s subversive and tantalising reflections.